Implementation of the Prototype Method in Developing a Questionnaire Information System for Integrated Survey Services - Setiawan, Rhoedy; Romadhon, Zainur; Hakim, Alvin Rainaldy (Sistemasi: Jurnal Sistem Informasi, 2025)
The advancement of information technology has driven educational institutions to enhance the efficiency and quality of both academic and non-academic services through more integrated survey systems. Universitas Muria Kudus (UMK) still relies on manual survey methods, leading to data duplication, input errors, and delays in analysis. This study aims to design and develop a centralized questionnaire information system to improve survey management efficiency. Using the prototype method, the system was developed in two cycles: the first cycle included core features such as a dashboard, questionnaire management, reporting, and a login system, while the second cycle refined functionalities, including input validation, answer variations, search filters, and report export capabilities. BlackBox Testing was conducted to ensure optimal system functionality. The results indicate that the proposed system enhances efficiency, minimizes data errors, and accelerates survey result analysis, ultimately contributing to improved academic and non-academic services at UMK.